Pengaruh Perceived Food Quality, Kepercayaan Konsumen, Kepuasan Konsumen, Dan Inovasi Produk Terhadap Repurchase Intention (Studi Kasus pada Konsumen Mie Horor Kepanjen) - Munawaroh, Mufrida; Rizal, Mohammad; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
This study aims to determine the effect of perceived food quality, consumer trust, consumer satisfaction, and product innovation on repurchase intention in consumers of Mie Horor Kepanjen. The sampling technique using purposive sampling obtained a sample of 90 respondents. Data collection method using questionnaires. The data analysis technique carried out in this study is multiple linear regression. The results showed that simultaneously perceived food quality, consumer trust, consumer satisfaction, and product innovation towards repurchase intention in consumers of Mie Horor Kepanjen. In addition, this study shows that partially perceived food quality has a positive and significant effect on repurchase intention in consumers of Mie Horor Kepanjen. However, partially consumer confidence, consumer satisfaction, and product innovation have a positive but not significant effect on the repurchase intention of Mie Horor Kepanjen consumers. Keywords: Perceived Food Quality, Consumer Trust, Consumer Satisfaction, And Product Innovation, Repurchase Intention.